Fungal Degradation of Extractives Plays an Important Role in the Brown Rot Decay of Scots Pine Heartwood - Belt, Tiina; Harju, Anni; Kilpeläinen, Petri; Venäläinen, Martti (Frontiers in Plant Science, 2022)
Scots pine heartwood is known to have resistance to wood decay due to the presence of extractives, namely stilbenes and resin acids. However, previous studies have indicated that these extractives are degradable by wood decaying fungi. This study aimed to investigate the relationship between extractive degradation and heartwood decay in detail and to gain insight into the mechanisms of extractive degradation. Mass losses recorded after a stacked-sample decay test with brown rot fungi showed that the heartwood had substantial decay resistance against Coniophora puteana but little resistance against Rhodonia placenta. Extracts obtained from the decayed heartwood samples revealed extensive degradation of stilbenes by R. placenta in the early stages of decay and a noticeable but statistically insignificant loss of resin acids. The extracts from R. placenta-degraded samples contained new compounds derived from the degraded extractives: hydroxylated stilbene derivatives appeared in the early decay stages and then disappeared, while compounds tentatively identified as hydroxylated derivatives of dehydroabietic acid accumulated in the later stages. The degradation of extractives was further analysed using simple degradation assays where an extract obtained from intact heartwood was incubated with fungal mycelium or extracellular culture fluid from liquid fungal cultures or with neat Fenton reagent. The assays showed that extractives can be eliminated by several fungal degradative systems and revealed differences between the degradative abilities of the two fungi. The results of the study indicate that extractive degradation plays an important role in heartwood decay and highlight the complexity of the fungal degradative systems.